KNOWLEDGE OF CARDIO-PULMONARY RESUSCITATION AMONG FIRST-YEAR NURSING STUDENTS - ASHRAF , R; JAVED , H; SADDIQUE, H; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
: In the dynamic realm of healthcare, proficiency in cardiopulmonary resuscitation (CPR) stands as a cornerstone skill for nursing professionals. First-year nursing students represent the future frontline caregivers entrusted with the critical responsibility of preserving human life during emergencies. Methods: A descriptive cross-sectional study was conducted from January to April 2024 at the Superior University Department of Nursing in Lahore, to assess CPR knowledge among first-year nursing students. The study, involving 80 participants selected through convenient sampling, included students without prior CPR training. Data was collected using a demographic questionnaire and a CPR Knowledge Questionnaire, with scores ranging from 0 to 77. Analysis was performed using SPSS 25.Results: The results of the study provide a comprehensive overview of the participants' demographics and their knowledge about CPR. Most participants were under 30 years old (91.3%), with nearly equal numbers living in hostels (48.8%) and as day scholars (51.2%). A significant majority were single (95%). Knowledge about CPR varied, with 53.8% of participants having average knowledge and 46.3% having good knowledge. Responses revealed varying levels of understanding about CPR's purpose, procedures, and effectiveness, highlighting a need for improved education and training. Conclusion: The study shows that most nursing students are under 30 years old, with a near-equal distribution between hostel residents and day scholars, and a majority are single. Overall, 53.8% have average CPR knowledge, while 46.3% have good knowledge.